Brain-specific src oncogene mRNA mapped in rat brain by in situ hybridization. - Ross, C A (1988)
Brain src protooncogene is expressed in two forms, one identical to message in other tissues, and one containing an 18-nucleotide insert specific to brain. We have mapped mRNA for the two forms of src in rat brain with selective antisense oligonucleotide probes to the brain (src+) and peripheral (src-) forms. Fetal rat src mRNA levels were much higher in the central nervous system than any peripheral organ. In adult brain, src+ mRNA level was highest in the internal granular layer of the olfactory bulb, pyramidal cells of the hippocampus, granule cells of the dentate gyrus, and cerebellar granule cells. src+ and src- levels were similar in hindbrain, but src+ levels were higher than those of src- in forebrain. These distributions suggest that src+ may play roles in a number of neural processes, possibly including neuronal plasticity.